Penyuluhan Hukum Penyusunan Rancangan Peraturan Desa Tentang Pengelolaan Sampah di Desa Beririjarak Kecamatan Wanasaba Lombok Timur - Yuni Ristanti; Beverly Evangelista; Ahwan; Suheflihusnaini Ashady; Nathania Permata S; Febrihadi Suparidho; Zahratul Ain Taufik (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
This community service activity aims to provide legal counseling related to the preparation of the Draft Village Regulation (Raperdes) on Waste Management in Beririjarak Village, Wanasaba District, East Lombok. The counseling is aligned with the provisions of the Regional Regulation of West Nusa Tenggara Province Number 15 of 2019 concerning Waste Management. The problem of waste management in Beririjarak Village has long been an issue that has given rise to pros and cons. The activity was carried out using lecture methods, participatory discussions, and technical assistance in preparing the Raperdes text. The results of the activity show that village officials and the community have gained a better understanding of the legal basis, principles of waste management, and procedures for preparing village regulations in accordance with statutory techniques. The output of the activity is an initial draft of the Raperdes on Waste Management and increased capacity of the village government in formulating legal policies at the local level.